2009
DOI: 10.1095/biolreprod.108.070102
|View full text |Cite|
|
Sign up to set email alerts
|

Preimplantation Embryo Development in the Mouse Requires the Latency of TRP53 Expression, Which Is Induced by a Ligand-Activated PI3 Kinase/AKT/MDM2-Mediated Signaling Pathway1

Abstract: A universal response to cellular stress is the expression of transformation-related protein 53 (TRP53). This transcription factor reduces cell proliferation and/or survival and is classed as a tumour suppressor protein. Several stresses (including culture) cause increased TRP53 expression in blastocysts and their reduced long-term developmental potential. This study shows that culture from the zygote stage (but not the 2-cell stage) reduced the development of C57BL6 inbred (but not hybrid) strain mouse embryos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 55 publications
1
45
0
Order By: Relevance
“…Stress-induced upregulation of p53 has been shown to result in developmental arrest of preimplantation embryo [44]. The latency of p53 in preimplantation embryo is well-documented to be maintained by autocrine stimulation through PI3K/Akt/Mdm2 pathway [43]. In this study, we have demonstrated an alternative pathway regulating the latency of p53 through HCO 3 − /CFTR-dependent miR-125b activation.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Stress-induced upregulation of p53 has been shown to result in developmental arrest of preimplantation embryo [44]. The latency of p53 in preimplantation embryo is well-documented to be maintained by autocrine stimulation through PI3K/Akt/Mdm2 pathway [43]. In this study, we have demonstrated an alternative pathway regulating the latency of p53 through HCO 3 − /CFTR-dependent miR-125b activation.…”
Section: Discussionmentioning
confidence: 57%
“…The HCO 3 − -dependent miR-125b activation is physiologically important for early embryo development by targeting p53 and its downstream target p21. It has been previously demonstrated that the latency of p53 is required for normal preimplantation embryo development [43]. Stress-induced upregulation of p53 has been shown to result in developmental arrest of preimplantation embryo [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAF may be important for implantation and maternal recognition of pregnancy (O'Neill, 1991) and enhances mitoses in preimplantation embryos in mice (Roberts et al, 1993). Paf generates a pro-survival anti-apoptotic transcriptome within the embryo (Jin and O'Neill, 2011) and maintains the tumour suppressor protein P53 in a latent state (Jin et al, 2009). In the tammar, PAF is present in the culture media after incubation of endometrial explants during embryonic diapause and at all reactivation stages examined (Kojima et al, 1993).…”
Section: Paf and Paf-receptormentioning
confidence: 99%
“…In the mouse, the addition of Paf can stimulate embryo metabolism (Ryan et al 1989(Ryan et al , 1990a, increase total cell number (Ryan et al 1990b, Roudebush et al 1996 and promote overall embryo development and viability (Nishi et al 1995, Stoddart et al 1996, O'Neill 1997, 1998. Furthermore, Paf has the critical function of generating a pro-survival antiapoptotic transcriptome within the embryo (Jin & O'Neill 2011) and has the net effect of maintaining the tumour suppressor protein p53 in a latent state (Jin et al 2009). However, exposure to high levels of Paf provides either no additional benefit or can even have harmful effects (Ryan et al 1990b).…”
Section: Introductionmentioning
confidence: 99%